An exploration of the interdependencies betweeen the real exchange rate andthe size of the tradable sector in a small open economy - Zarzosa Valdivia, Fernando (2022)
Fil: Zarzosa Valdivia, Fernando. Universidad Nacional de Córdoba; Argentina